2021
DOI: 10.1167/iovs.62.7.11
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-3 Mediates Metabolic Homeostasis During Hyperosmolar Stress in the Corneal Epithelium

Abstract: Purpose The insulin-like growth factor binding protein-3 (IGFBP-3) is a multifunctional secretory protein with well-known roles in cell growth and survival. Data in our laboratory suggest that IGFBP-3 may be functioning as a stress response protein in the corneal epithelium. The purpose of this study is to determine the role of IGFBP-3 in mediating the corneal epithelial cell stress response to hyperosmolarity, a well-known pathophysiological event in the development of dry eye disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
4
10
0
Order By: Relevance
“…To determine whether IGFBP-3 impacts cell growth in cells exposed to hyperosmolar stress, hTCEpi cells were cultured in KBM under isotonic or hyperosmolar conditions (450 mOsm), with or without 500 ng/mL rhIGFBP-3 for six or twenty-four hours. Consistent with our prior work, six hours of hyperosmolar culture arrested hTCEpi cells in the G2/M phase ( Figure 2 A, p < 0.001) [ 41 ]. Unlike the beneficial effects on mitochondrial respiration, treatment with rhIGFBP-3 did not affect cell cycle or cell number ( Figure 2 A,B).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…To determine whether IGFBP-3 impacts cell growth in cells exposed to hyperosmolar stress, hTCEpi cells were cultured in KBM under isotonic or hyperosmolar conditions (450 mOsm), with or without 500 ng/mL rhIGFBP-3 for six or twenty-four hours. Consistent with our prior work, six hours of hyperosmolar culture arrested hTCEpi cells in the G2/M phase ( Figure 2 A, p < 0.001) [ 41 ]. Unlike the beneficial effects on mitochondrial respiration, treatment with rhIGFBP-3 did not affect cell cycle or cell number ( Figure 2 A,B).…”
Section: Resultssupporting
confidence: 91%
“…Similar to the effects of hyperosmolar stress on cells in culture, IGFBP-3 expression was decreased in the mouse corneal epithelium compared to control at all time points tested ( Figure 7 D, p < 0.001 compared to baseline). To further examine the effect of IGFBP-3 on corneal health, IGFBP-3 was topically applied to mouse corneas twice a day every other day for seven days [ 41 ]. Treatment was initiated after 21 days of DED.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In diabetic mice, Qu et al [ 27 ] demonstrated that hyperglycemia-induced mitochondrial bioenergetic inadequacy of the lacrimal gland ameliorates early onset of dry eye. Bogdan et al [ 28 ] proposed that insulin-like growth factor binding protein-3 (IGFBP-3) is involved in hyperosmolar stress responses in the corneal epithelium by modulating mitochondrial function. Hyperosmolarity can increase ROS and apoptosis of HCEpiCs ( Figure 1 ), and our results confirm this.…”
Section: Discussionmentioning
confidence: 99%